Public Policy Implementation As Political Clientelism: The Double Edge of The Smart Indonesian Card (KIP Kuliah) Program in West Sulawesi - Mappatunru, A.; Zainuddin, Sriwiyata Ismail (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2026)
In post-authoritarian Indonesia, the open-list proportional electoral system affords incumbent legislative candidates the opportunity to appropriate state budgetary patronage resources for personal, particularly electoral, objectives. This system reorients the primary focus of patronage politics from a party-voter dynamic to a candidate-voter relationship, thereby establishing informal networks as central to patronage distribution. This research investigates how an incumbent legislative candidate leverages informal networks to exert control over state policies, thereby redirecting the implementation of the Kartu Indonesia Pintar program toward clientelistic ends. Employing a qualitative case study with an explanatory orientation, the study draws upon interviews with beneficiaries, party administrators, and campaign teams, supplemented by documentary evidence from social media and online reports. The findings indicate that the implementation of the KIP Kuliah program has become a political arena where Fem-01 transcends her formal legislative authority, effectively acting as a de facto policy implementer. Through a shadow bureaucracy, Fem-01 mobilizes informal networks to capture the program’s implementation and cultivate long-term clientelistic ties with beneficiaries. Conceptually, this study contributes to the discourse on money politics by introducing the notion of ‘disguised money politics,’ defined as a subtle form of vote purchasing facilitated through state-funded welfare programs. The findings underscore how democratization has blurred the demarcation between bureaucratic procedures and informal politics, highlighting that policy implementation itself constitutes a political act extending beyond formal institutions.